Different roles of cyclic electron flow around photosystem I under sub-saturating and saturating light intensities in tobacco leaves - Huang, Wei; Yang, Ying-Jie; Hu, Hong; Zhang, Shi-Bao (Frontiers in Plant Science, 2015)
In higher plants, the generation of proton gradient across the thylakoid membrane (pH) through cyclic electron flow (CEF) has mainly two functions: 1) to generate ATP and balance the ATP/NADPH energy budget, and 2) to protect photosystems I and II against photoinhibition. The intensity of light under which plants are grown alters both CEF activity and the ATP/NADPH demand for primary metabolic processes. However, it is unclear how the role of CEF is affected by the level of irradiance that is applied during the growth and measurement periods. We studied the role of CEF at different light intensities in leaves from sun- and shade-grown plants. At 849 μmol photons m-2 s-1, both types of leaves had nearly the same degree of CEF activation. Modeling of the ATP/NADPH demand revealed that, at this light intensity, the contribution of CEF toward supplying ATP was much higher in the sun leaves. Meanwhile, the shade leaves showed higher levels of non-photochemical quenching and the P700 oxidation ratio. Therefore, at 849 μmol photons m-2 s-1, CEF mainly helped in the synthesis of ATP in the sun leaves, but functioned in photoprotection for the shade leaves. When the light intensity increased to 1976 μmol photons m-2 s-1, CEF activation was greatly enhanced in the sun leaves, but its contribution to supplying ATP changed slightly. These results indicate that the main role of CEF is altered flexibly in response to light intensity. In particular, CEF mainly contributes to balancing the ATP/NADPH energy budget under sub-saturating light intensities. When exposed to saturating light intensities, CEF mainly protects photosynthetic apparatus against photoinhibition.